Learning English through out-of-school exposure. Which levels of language proficiency are attained and which types of input are important?. Issue 1 (18th February 2019) - De Wilde, Vanessa; Brysbaert, Marc; Eyckmans, June
Abstract: In this study we examined the level of English proficiency children can obtain through out-of-school exposure in informal contexts prior to English classroom instruction. The second aim was to determine the input types that fuel children's informal language acquisition. Language learning was investigated in 780 Dutch-speaking children (aged 10–12), who were tested on their English receptive vocabulary knowledge, listening, speaking, reading and writing skills. Information about learner characteristics and out-of-school English exposure was gathered using questionnaires. The results show large language gains for a substantial number of children but also considerable individual differences. The most beneficial types of input were gaming, use of social media and speaking. These input types are interactive and multimodal and they involve language production. We also found that the various language tests largely measure the same proficiency component.